The venom of Cyriopagopus schmidti spider contains a natural huwentoxin-IV analogue with unexpected improved analgesic potential - Aurélie Antunes; Aurélie Antunes; Aurélie Antunes; Jérôme Montnach; Kuldip Khakh; Ludivine Lopez; Baptiste Thomas; Barbara Ribeiro Oliveira-Mendes; Lucie Jaquillard; Denis Servent; Rémy Béroud; Rémy Béroud; et al. (Frontiers in Pharmacology)
The venom of Cyriopagopus schmidti spider has been extensively investigated, thereby allowing the identification of numerous new natural peptides. Many of these peptides are active on ion channels and several of them occur from post-translational processing. In order to further identify new entities, we screened this venom against five different human voltage-gated sodium (hNav) channels. We illustrate the unusual richness of this venom in targeting this wide variety of hNav channels. We confirm the identity of previously discovered peptides active on these ion channels type (huwentoxin (HwTx)-I, HwTx-II and HwTx-IV), indicating the efficacy of the screening process by automated patch-clamp. We also identified a novel analogue of HwTx-IV that differs by the absence of amidation and the presence of an extra C-terminal Gly residue. Interestingly, this analogue is less potent than HwTx-IV itself in blocking hNav1.7 in cell lines, but turns out to be significantly more potent in TTX-sensitive dorsal root ganglia neurons. Because of this unexpected finding, this novel analogue turns out to be a more potent analgesic than HwTx-IV itself without presenting most of the Nav1.6-related toxic effects of HwTx-IV.